Escherichia coli resistance patterns, empiric and targeted antibiotic prescriptions in children: a single center experience - Buonsenso, Danilo; Pata, Davide; Fiori, Barbara; Sanguinetti, Maurizio; Acampora, Anna; Ferrari, Vittoria; Albano, Rossana; Spanu, Teresa; Valentini, Piero (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Antibiotic resistance represents one of the major public health issues, due to the potential future ineffectiveness of available antibiotics. However, epidemiological studies on E. coli antibiotic resistance patterns in the pediatric population are limited. Methods: We conducted a retrospective analysis on children younger than 18 years of age admitted to the Department of Pediatrics from April 2016 to April 2018 with E. coli isolation on biological materials. Results: 205 subjects were included in the study (mean age 1.6 years). We found an overall low rate of resistance of E. coli isolates to Amoxicil-lin/Clavulanate (20%), Cephalosporins (6.3%) and Aminoglycosides (6.3%), while no isolates were resistant to Carbapenems. Presence of invasive devices and intensive care admissions were as-sociated with resistance to Cephalosporines (P < 0.001; OR 9.21, 95% CI 2.7 – 31.39) and Amino-glycosides (P < 0.004; OR 5.42, 95% CI 1.71 – 17.15), while no factors associated with resistance to the other antibiotics were found. Conclusions: Aminoglycosides and Cephalosporins were frequently used as empiric therapy, whereas targeted therapies aimed at sparing these classes of antibiotics once antibiograms were available have not always been established. These data may inform local antimicrobial stewardship and guide the development of programs aiming at a better use of antibiotics.